Direct Observation of Domain-Wall Configurations Transformed by Spin Currents - Kläui, Mathias; Jubert, Pierre-Olivier; Allenspach, Rolf; Bischof, Andreas; Bland, J. Anthony C.; Faini, Giancarlo; Rüdiger, Ulrich; Vaz, Carlos A. F.; Vila, Laurent; Vouille, Carole (My University, 2005)
Direct observations of current-induced domain-wall propagation by spin-polarized scanning electron microscopy are reported. Current pulses move head-to-head as well as tail-to-tail walls in submicrometer Fe20Ni80 wires in the direction of the electron flow, and a decay of the wall velocity with the number of injected current pulses is observed. High-resolution images of the domain walls reveal that the wall spin structure is transformed from a vortex to a transverse configuration with subsequent pulse injections. The change in spin structure is directly correlated with the decay of the velocity.
Keywords: 530; 72.25.Ba; 75.60.Ch; 75.75.+a